A brief history of QIRT concept, structures and community. Issue 1 (2nd January 2016) - Balageas, Daniel L.
Abstract : With the XIIth QIRT conference held in 2014 and the first QIRT-Asia conference this year, it seems opportune to give a brief history of QIRT activities. The context of the birth of the QIRT conference and the ideas which were behind are first recalled. Then, the successive conferences are evoked thanks to statistic figures. In a second part, it is shown that QIRT is not only a conference, but a structure which covers different types of activities. Its heart is the QIRT Steering Committee which watches over the QIRT conferences, QIRT journal, a permanent QIRT Website and QIRT Open Archives in which all communications at the QIRT conferences are maintained available for free loading. Finally, the possible future evolution of QIRT activities is envisaged.